Nutrient salvaging and metabolism by the intracellular pathogen Legionella pneumophila - Fonseca, Maris V.; Swanson, Michele S. (Frontiers in Cellular and Infection Microbiology, 2014)
The Gram-negative bacterium Legionella pneumophila is ubiquitous in freshwater environments as a free-swimming organism, resident of biofilms, or parasite of protozoa. If the bacterium is aerosolized and inhaled by a susceptible human host, it can infect alveolar macrophages and cause a severe pneumonia known as Legionnaires’ disease. A sophisticated cell differentiation program equips L. pneumophila to persist in both extracellular and intracellular niches. During its life cycle, L. pneumophila alternates between at least two distinct forms: a transmissive form equipped to infect host cells and evade lysosomal degradation, and a replicative form that multiplies within a phagosomal compartment that it has retooled to its advantage. The efficient changeover between transmissive and replicative states is fundamental to L. pneumophila’s fitness as an intracellular pathogen. The transmission and replication programs of L. pneumophila are governed by a number of metabolic cues that signal whether conditions are favorable for replication or instead trigger escape from a spent host. Several lines of experimental evidence gathered over the past decade establish strong links between metabolism, cellular differentiation and virulence of L. pneumophila. Herein, we focus on current knowledge of the metabolic components employed by intracellular L. pneumophila for cell differentiation, nutrient salvaging and utilization of host factors. Specifically, we highlight the metabolic cues that are coupled to bacterial differentiation, nutrient acquisition systems, and the strategies utilized by L. pneumophila to exploit host metabolites for intracellular replication.